Development of Fire and Temperature Monitoring Interface in The Engine Room Using Visual Basic Programming - Kusuma, Cahya; Kusdiana, Wawan; Syaifi, Muhammad; Ika, Aris Tri; Indiaryanto, Mahendra (International Journal of Marine Engineering Innovation and Research, 2025)
The design of the Temperature and Fire Monitoring Interface using Visual Basic Programming aims to detect fires at any time on the ship, especially in the main engine and diesel generator rooms. If the ship's initial conditions in the Main Engine room and diesel generator room are created to cause a fire, the tool will send a fire hazard signal which can be directly monitored by the ship's crew so that prevention can be carried out as early as possible. This design uses two smoke sensors and temperature sensors as inputs, one Arduino Uno microcontroller as a controller, one PC / Laptop as an interface for monitoring temperature and smoke conditions. The result of this system is that if the input temperature sensor and smoke sensor do not detect a fire hazard, the interface output displays a green color. If the temperature and smoke sensor input detects a fire hazard, the interface output will print red, and the buzzer output will light up as set by a visual basic program.